A reply to Sahle and Braun's reply to 'The pattern of emergence of a Middle Stone Age tradition at Gademotta and Kulkuletti (Ethiopia) through convergent tool and point technologies' [J. Hum. Evol. 91 (2016) 93–121]. Issue 125 (December 2018) - Douze, Katja; Delagnes, Anne; Rots, Veerle; Gravina, Brad
Abstract: Sahle and Braun's (in press) recent comments on our identification (Douze and Delagnes, 2016) of diachronic trends in Middle Stone Age point traditions in several lithic assemblages from the sites of Gademotta and Kulkuletti (Ethiopia) focuses on pointed tool function rather than the gradual technological shifts we observed between sites. Here we address several of what we consider to be inaccuracies and misinterpretations concerning our work with the Gademotta and Kulkuletti lithic assemblages (Douze, 2012, 2014), more specifically, Sahle and Braun's (in press) interpretation of the tranchet blow technique. This discussion is inseparable from a critical review of the evidence advanced by Sahle and Braun to support projectile technology being present in the Gademotta Formation as early as >279 ka.